PENGEMBANGAN MODUL INTRERAKTIF UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS V SDN 7 MEMPAWAH HILIR KABUPATEN MEMPAWAH - Wahyu Wahyu; Aloysius Mering; Fadillah Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThe development of an interactive module based on the low learning outcomes of students as well as students has difficulty in developing speaking skills due to lack of exercise and the material in the package book is not complete, so that students are not used to skilled in speaking. The purpose of developing an interactive module to produce instructional media used independently by students. The development research procedure taken from Borg and Gall consists of 10 steps: data collection, planning, product development, expert validation, revision of expert comments, trials, revisions of comments, and final product improvements. Data collection techniques with observation, interviews, and documents. The research instruments are observation sheet, interview guide, and questionnaire. Data analysis using qualitative and quantitative. The result of the module has been constructed through research and development, has been tested able to improve students' speaking ability. This is evidenced by the increase. Improving students' speaking skills using interactive module shows improvement, this is seen from pretest result 68,63 while posttest result 77,22. The increase can also be seen from the 2 paired sample t test that shows the value of t arithmetic> t table (11,09> 1,708), it means there is improvement of student's speaking skill using interactive module.This module can be used for Indonesian language speaking aspectKeywords: interactive module, speaking skill, skill enhancement